Bioplastics for food packaging: environmental impact, trends and regulatory aspects - Cruz, Rui (2022)
The demand to develop and produce eco-friendly alternatives for food packaging is increasing. The huge negative impact that the disposal of so-called “single-use plastics” has on the environment is propelling the market to search for new solutions, and requires initiatives to drive faster responses from the scientific community, the industry, and governmental bodies for the adoption and implementation of new materials. Bioplastics are an alternative group of materials that are partly or entirely produced from renewable sources. Some bioplastics are biodegradable or even compostable under the right conditions. This review presents the different properties of these materials, mechanisms of biodegradation, and their environmental impact, but also presents a holistic overview of the most important bioplastics available in the market and their potential application for food packaging, consumer perception of the bioplastics, regulatory aspects, and future challenges.